Bibliometric analysis of pyroptosis in pathogenesis and treatment of acute lung injury - Wang, Chun; Liu, Na (Frontiers in Medicine, 2025)
ObjectiveThis study aims to conduct a bibliometric analysis to assess the present state, thematic focus, and emerging developments in the research literature on the involvement of pyroptosis in the pathogenesis and treatment of acute lung injury (PFALI), as well as other pertinent research areas.MethodsThis bibliometric study examined PFALI research published from 1 January 2004 to 24 May 2024, utilizing the Web of Science database. The analysis was conducted using CiteSpace, VOSviewer, R, and GraphPad Prism 8.0, and encompassed metadata on the countries, institutions, authors, journals, and keywords represented in the literature.ResultsThis study analyzed 1,495 publications, comprising 1,194 articles and 301 reviews, to assess the publication output on PFALI. China exhibited the highest output with 964 (64.48%) articles. Central South University was the most prolific institution, contributing 54 (3.61%) publications. Zhou, Yong had the greatest individual publication record, with 15 (3.59%) articles. The journal International Immunopharmacology published the most PFALI-related articles at 76 (5.09%). The identified research frontiers for upcoming years include “iron,” “sirt1,” “repair,” and “alveolar macrophage pyroptosis.”ConclusionThis bibliometric analysis comprehensively examined research trends and advancements related to PFALI, including the contributions of key authors, institutions, and countries.